2010
DOI: 10.1038/nature09455
|View full text |Cite
|
Sign up to set email alerts
|

An amorphous solid state of biogenic secondary organic aerosol particles

Abstract: Secondary organic aerosol (SOA) particles are formed in the atmosphere from condensable oxidation products of anthropogenic and biogenic volatile organic compounds (VOCs). On a global scale, biogenic VOCs account for about 90% of VOC emissions and of SOA formation (90 billion kilograms of carbon per year). SOA particles can scatter radiation and act as cloud condensation or ice nuclei, and thereby influence the Earth's radiation balance and climate. They consist of a myriad of different compounds with varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

40
819
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 759 publications
(876 citation statements)
references
References 27 publications
40
819
1
Order By: Relevance
“…In this context, well-mixed means behavior consistent with complete compositional uniformity. Recent studies [3][4][5][6] suggest that some organic aerosols exist in a glassy or semisolid phase, which can significantly affect the rates and mechanisms of the uptake of water 7,8 and other gas phase species as well as heterogeneous oxidation chemistry. 1 Laboratory studies of model systems are essential to unravel these factors and provide a rigorous foundation for climate model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, well-mixed means behavior consistent with complete compositional uniformity. Recent studies [3][4][5][6] suggest that some organic aerosols exist in a glassy or semisolid phase, which can significantly affect the rates and mechanisms of the uptake of water 7,8 and other gas phase species as well as heterogeneous oxidation chemistry. 1 Laboratory studies of model systems are essential to unravel these factors and provide a rigorous foundation for climate model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…An aerosol's viscous state also has direct implications on the particle morphology, phase behaviour, optical properties, aging processes and lifetime. At the same time, only few direct measurement methods are available for monitoring such properties 1, [6][7][8][9][10][11][12][13][14][15][16] . Recently, we have demonstrated that viscosity of model organic aerosols, such as oleic acid droplets, and secondary organic aerosols (SOA) produced from the oxidation of myrcene or -pinene can be measured and imaged in a spatially and time-resolved manner using Fluorescence Lifetime Imaging Microscopy (FLIM) of molecular rotors 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Physical properties of particles, such as hygroscopicity, size, density, phase, elasticity, and hardness, play an important role in particle bounce behavior (Wall et al 1990;Stein et al 1994;Matthew et al 2008;Virtanen et al 2010;Virtanen et al 2011;Bateman et al 2014). Hygroscopic particles, such as salts, are known to have much less bounce than non-hygroscopic particles (Stein et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory and field tests reported that a CE of less than 100% was mainly caused by particle bounce from the vaporizer, especially for solid particles (Jayne et al 2000;Huffman et al 2005;Quinn et al 2006;Liu et al 2007;Salcedo et al 2007). In addition, particle bounce has been considered as an important issue for impactor techniques that use the inertial force of particles (i.e., high impaction velocity) for sampling or separation (Virtanen et al 2010;Bateman et al 2014).…”
Section: Introductionmentioning
confidence: 99%